Pondok Pesantren Merupakan Sebuah Sistem Dalam Pendidikan Islam - Abdul Hadi (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
As the basis of Islamic education, Islamic boarding schools can indeed be said to be strategic places in giving birth to scholars, clerics, and even big figures who have a high understanding of the religion of Islam. The research method used is library research or library research. Meanwhile, what is meant by literature review research is a study carried out to solve a problem which basically relies on critical and in-depth research on relevant library materials. Library materials are used to explore new ideas as the basis for carrying out deductions from existing knowledge. As an Islamic educational institution, pesantren from a historical cultural point of view can be said to be a